Spatial Changes Under Global Warming: A Review of GIS Applications in Climate Change Research - Chen, Yixi (Transactions on Environment, Energy and Earth Sciences, 2024)
This paper explores the pressing global challenge —climate change— from a GIS perspective. This issue has already disrupted the natural world, forcing changes within our human society, and is predicted to become an even more urgent matter to be addressed. Utilizing GIS, it provides researchers with another lens for investigating the trends and impacts of climate change even modeling future scenarios. The paper focuses on three aspects including rising temperature, sea level changes, and extreme weather events. Through discussing the role of GIS and delving into specific case studies the application of this power technology will be reviewed, highlighting the ability of GIS to incorporate vast volume and variety of data. Explaining the different approaches that can be used when this advanced yet complex tool of visualization and spatial analysis is involved. However, limitations including data accuracy and model uncertainty are also identified indicating that there is more potential that lies ahead in supplementing GIS findings with climate research and policy development.